Loss of Inositol Phosphorylceramide Sphingolipid Mannosylation Induces Plant Immune Responses and Reduces Cellulose Content in Arabidopsis. Issue 12 (28th November 2016) - Fang, Lin; Ishikawa, Toshiki; Rennie, Emilie A.; Murawska, Gosia M.; Lao, Jeemeng; Yan, Jingwei; Tsai, Alex Yi-Lin; Baidoo, Edward E.K.; Xu, Jun; Keasling, Jay D.; Demura, Taku; Kawai-Yamada, Maki; et al.
Abstract : Identification and characterization of a putative Arabidopsis sphingolipid glycosyltranferase suggests that glycosylation of these crucial lipids affects cellulose content and plant defense signaling. Abstract: Glycosylinositol phosphorylceramides (GIPCs) are a class of glycosylated sphingolipids found in plants, fungi, and protozoa. These lipids are abundant in the plant plasma membrane, forming ∼25% of total plasma membrane lipids. Little is known about the function of the glycosylated headgroup, but two recent studies have indicated that they play a key role in plant signaling and defense. Here, we show that a member of glycosyltransferase family 64, previously named ECTOPICALLY PARTING CELLS1, is likely a Golgi-localized GIPC -specific mannosyl-transferase, which we renamed GIPC MANNOSYL-TRANSFERASE1 (GMT1). Sphingolipid analysis revealed that the Arabidopsis thaliana gmt1 mutant almost completely lacks mannose-carrying GIPCs. Heterologous expression of GMT1 in Saccharomyces cerevisiae and tobacco ( Nicotiana tabacum ) cv Bright Yellow 2 resulted in the production of non-native mannosylated GIPCs. gmt1 displays a severe dwarfed phenotype and a constitutive hypersensitive response characterized by elevated salicylic acid and hydrogen peroxide levels, similar to that we previously reported for the Golgi-localized, GIPC -specific, GDP-Man transporter GONST1 (Mortimer et al., 2013 ). Unexpectedly, we show that gmt1 cell walls have a reduction in cellulose content, although other matrix polysaccharides are unchanged.